Seed-shattering phenology at soybean harvest of economically important weeds in multiple regions of the United States. Part 3: Drivers of seed shatter. Issue 1 (15th January 2022) - Schwartz-Lazaro, Lauren M.; Shergill, Lovreet S.; Evans, Jeffrey A.; Bagavathiannan, Muthukumar V.; Beam, Shawn C.; Bish, Mandy D.; Bond, Jason A.; Bradley, Kevin W.; Curran, William S.; Davis, Adam S.; Everman, Wesley J.; Flessner, Michael L.; et al.
Abstract: Seed retention, and ultimately seed shatter, are extremely important for the efficacy of harvest weed seed control (HWSC) and are likely influenced by various agroecological and environmental factors. Field studies investigated seed-shattering phenology of 22 weed species across three soybean [ Glycine max (L.) Merr.]-producing regions in the United States. We further evaluated the potential drivers of seed shatter in terms of weather conditions, growing degree days, and plant biomass. Based on the results, weather conditions had no consistent impact on weed seed shatter. However, there was a positive correlation between individual weed plant biomass and delayed weed seed–shattering rates during harvest. This work demonstrates that HWSC can potentially reduce weed seedbank inputs of plants that have escaped early-season management practices and retained seed through harvest. However, smaller individuals of plants within the same population that shatter seed before harvest pose a risk of escaping early-season management and HWSC.